The Use of Trade Association Disclosures by Investors and Analysts: Evidence from the Semiconductor Industry* - CHANDRA, UDAY; PROCASSINI, ANDREW; WAYMIRE, GREGORY (Contemporary Accounting Research, 1999)
Abstract This paper investigates the relation between industry‐wide information disclosures by the trade association for the semiconductor industry and both share prices and analyst forecasts. Such disclosures may have little impact on investors and analysts, since prior theoretical research suggests that trade associations may be unable to secure reliable data from firms in an industry. At the same time, such disclosures may be important, since prior empirical research suggests that share prices and analyst forecasts reflect industry‐wide earnings effects earlier than firm‐specific effects. We document significant stock price movements on release dates of industry Flash Reports by the Semiconductor Industry Association (SIA) each month that contain aggregate industry data on new orders and shipments. The magnitude of the price revisions on Flash Report disclosure dates is positively associated with changes in the numbers disclosed and varies across sample firms in a manner associated with identifiable characteristics of the firms. Further tests indicate that the Flash Report provides mainly forward‐looking information on new orders that is linked to firm‐specific sales changes and has explanatory power for quarterly stock prices beyond firm‐specific earnings. This information is used by security analysts mainly in assessing the persistence of firm‐specific quarterly sales changes. Our findings support the hypothesis that the SIA is able to obtain data from firms, compile it into reliable aggregate statistics, and then distribute these statistics in a timely fashion.